ZnT8 Arg325Trp polymorphism influences zinc transporter expression and cytokine production in PBMCs from patients with diabetes. (October 2018) - Giacconi, R.; Malavolta, M.; Chiodi, L.; Boccoli, G.; Costarelli, L.; Bonfigli, A.R.; Galeazzi, R.; Piacenza, F.; Basso, A.; Gasparini, N.; Nisi, L.; Testa, R.; et al.
Abstract: Aims: ZnT8 Arg325Trp polymorphism has been associated with type 2 diabetes (T2DM) susceptibility. The Arg-325 risk variant shows accelerated zinc (Zn) transport kinetic and reduced glucose-stimulated insulin secretion in pancreatic cells. However, it remains unexplored the role of Znt8 polymorphism in the regulation of Zn homeostasis and inflammatory response in peripheral blood mononuclear cells (PBMCs) from T2DM patients. Methods and results: A total of 556 healthy controls and 413 T2DM patients were genotyped for ZnT8 Arg325Trp polymorphism confirming the association of Arg-325 variant with an increased T2DM risk (OR = 1.35 95% C.I: 1.10–1.66; p = 0.0044). Moreover, PBMCs from Arg/Arg T2DM subjects showed increased intracellular free Zn, higher gene expression of Metallothioneins, Znt1, Znt8, Zip2 genes, and reduced Znt4 and Znt7. Higher release of IL-1α, IL-1β, IFN-γ, IL-12p70 and TNF-α and a reduced IL-10 secretion after lipopolysaccharide (LPS) stimulation were observed in PBMCs from Arg/Arg T2DM carriers as compared to subjects with the Trp variant. Conclusions: Our data provide evidence of a substantial different Zn homeostasis regulation between Znt8 Arg-325 and Trp-325 carriers in PBMCs from T2DM patients. Moreover, Znt8 Arg-325 risk variant shows an enhanced inflammatory response upon LPS stimulation that might aggravate insulin resistance and the progression of diabetes cardiovascular complications.